Stress tolerance of Antarctic macroalgae in the early life stages - Navarro Martinez, Nelso Patricio; Huovinen, Pirjo; Gomez, Ivan (My University, 2016)
BACKGROUND: Early life stages of macroalgae, especially from polar species, can be highly vulnerable to physical stressors, leading to important consequences for the fate of the whole population in scenarios of changing environmental variability. In the present study, tolerance to UV and temperature stress, as measured by rapid adjustment of photochemistry, Fv/Fm, and photosynthetic characteristics based on P-E curves (ETRmax, α and Ek), was assessed in the early life stages of six Antarctic macroalgal species from eulittoral (Pyropia endiviifolia, Iridaea cordata, Adenocystis utricularis and Monostroma hariotii) and sublittoral (Ascoseira mirabilis and Gigartina skottsbergii. RESULTS: Reproductive cells of eulittoral species showed the highest light demands (Ek >45 μmol photon m-2 s-1) when compared to those from sublittoral species (Ek<30 μmol photon m-2 s-1). Short-term experiments of 1 h revealed that reproductive cells of P. endiviifolia, A. utricularis and M. hariotii had the highest temperature tolerance with a decrease of Fv/Fm observed only at 30 °C, while carpospores of G. skottsbergii exhibited the highest sensitivity to temperature increase with a decrease of Fv/Fm, which could be observed at 5 °C. UV tolerance was observed in reproductive cells of the eulittoral species with < 20 % inhibition in Fv/Fm from UV after four hours of exposure, while sublittoral species were more sensitive with >30 % inhibition in Fv/Fm in the same condition. Enhanced temperature (7 and 12 °C) improved the tolerance of I. cordata compared to 2 °C, but exacerbated the detrimental effects of UV on A. mirabilis. CONCLUSION: Results showed that photosynthetic characteristics varied among reproductive cells of different species, reflecting the vertical zonation of parental thalli. Otherwise, these differences appear to underlie biogeographical and evolutionary components. In addition, UV tolerance was modulated by temperature increase, while temperature increase, in turn, ameliorated the detrimental effects of stress treatments in some eulittoral species (I. cordata tetraspores). In sublittoral A. mirabilis gametangia, temperature exacerbated the reduction of photosynthetic efficiency.
Keywords: antarctica; reproductive cells; seaweeds; temperature; uv tolerance